(3GdJfbjM GdQGFY aj TQM eNJUQ GdTQGFYs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYXje (B... (3hHYO aEf Yde Gdabg dG jNai HdhZg(B...s
(3BNQgG (B:s
(3dG jYde GdJgeI dCfgG djSJ MGUdI aj faS GdCeQ (B... (3hdjcf gPG BNQ GdeLdO GdChd ef GdJfbjM(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B470s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis